User requirements and quality assessment on shoe size and fit recommendation - Afiqah Shuhada Abu Hasan Asari; Nurulhuda Noordin; Anitawati Mohd Lokman; Norzehan Sakamat; Mohd Firdauz Mohd Fathir (Penerbit Universiti Kebangsaan Malaysia, 2023)
Online shoppers often have to find reference conversion by manual method, standalone systems, asking sales agents, and browsing the internet. However, these methods that did not provide fast and seamless information on size and fit, and what more by different brands. This study was conducted to identify user requirements for shoe sizing and fitting based on standard size conversion (US, UK, Euro), brand and type. A survey (n=62) was conducted with online shoppers to determine functional and non-functional requirements for the shoe size and fit recommendation mobile application. Subsequently, a mobile application was developed based on the output, followed by 15 user satisfaction tests (n=50) to assess its quality using 9 task scenarios. An interview was then conducted to obtain richer user feedback. The analysis showed more than 90% of users evaluated the application as easy to use, had a pleasant interface, had the intention of using it, would recommend it to others, and were satisfied with the overall application. The mean analysis showed a score of 4.6, which indicates that most of the participants were satisfied with the application. The interview results suggested the application to add brand recommendations and customize features for children’s shoes. These open opportunities for future work to improve the acceptance and quality of the application. Users who wish to buy shoes online could benefit from the application by finding the right fit based on foot size, shoe brand and type easily using their smartphone.